Diagnóstico e implementación de un plan de mejora del clima laboral para incrementar la satisfacción de los colaboradores del área de atención ciudadana de una institución pública, de octubre 2015 a marzo de 2016. - Lema Moyón, Viviana Elizabeth (2016)
The present objective is to diagnose the work environmet of the workers the area of citizen in the public institution from october 2015 to march 2016, was very necessary know the different factors in the job performance of the workers according to the perception of each person of the manner it developed improvements plans in base of the necessity of the collaborators. Methodologically the research was designed in a quantitative method, also applied the research instruments used technique was a poll with nine factors it was applied to twelve works, moreover did a consultation process and direct observation to the collaborators. The results obtained show us that exist factors that should keep and others improve such as: comunication, leadership, take decisions, recognition and sanctions. For these factors established specific goals, solutions through activities, results and responsible person for getting the improvemnet plans. On the other hand, hope to achieve that the personal identify with the institution to your satisfaction and fulfillment of the goals also a healthy environment where the workers can develop personal and professionally, improving their skills.